Simple and rapid method on High Performance Liquid Chromatography for simultaneous determination of benzylpenicillin potassium, streptomycin sulphate and related substances in Ascomicin – a veterinary use ointment - Neagu Maria; Soceanu Georgiana; Bucur Ana Caterina (Medicamentul Veterinar, 2015)
A new simple, rapid, accurate and precise High – Performance Liquid Chromatography (HPLC) method for determination of benzylpenicillin potassium and streptomycin sulphate in Ascomicin ointment was developed and validated. The method can be used for the detection and quantification of known and unknown impurities and degradation products in this pharmaceutical product during routine analysis and also for stability studies in view of its capability to separate degradation products. The method was validated for accuracy, precision, specificity, robustness and quantification limits according to ICH Guidelines. The estimation of benzylpenicillin potassium and streptomycin sulphate was done by Waters HPLC 2695. The chromatographic conditions comprised a reverse-phased C18 column (5 µm particle size, 250 mm×4.6 mm i.d.) with a mobile phase consisting of a mixture of solution in water containing 0.025 M of sodium phosphate dibasic and 0.02 of sodium hexansulfonate adjusted to pH 6.0 with 22.5 g/lsolution of phosphoric acid and acetonitrile in gradient elution. The flow rate was 0.8 ml/min. Standard curves were linear over the concentration range of 5.00 µg/ml to 5.00 mg/ml for streptomycin sulphate and 3.26 µg/ml to 3.26 mg/ml for benzylpenicillin potassium. Statistical analyses proved the method was precise, reproducible, selective, specific and accurate for analysis of benzylpenicillin potassium, streptomycin sulphate and related substances.